2020
DOI: 10.1101/2020.08.02.233023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systemic and Molecular Study of Subcellular Localization of SARS-CoV-2 Proteins

Abstract: Coronavirus possesses the largest RNA genome among all the RNA viruses. Its genome encodes about 29 proteins. Most of the viral proteins are non-structural proteins (NSP) except envelop (E), membrane (M), nucleocapsid (N) and Spike (S) proteins that constitute the viral nucleocapsid, envelop and surface. We have recently cloned all the 29 SARS-CoV-2 genes into vectors for their expressions in mammalian cells except NSP11 that has only 14 amino acids (aa). We are able to express all the 28 cloned SARS-CoV-2 gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 39 publications
(29 reference statements)
4
53
2
Order By: Relevance
“…Nsp14 may manipulate IMPDH2 to increase the phosphorylation of IKKβ and IκBα to promote nuclear translocation and phosphorylation of p65 (24). In addition, we also noticed that Nsp14 partially localizes in the nuclei of cells (Fig 1C, D), similar to findings from other groups (51,52). Thus, Nsp14 may associate with and modify the host cellular RNAs via its exonuclease and methyltransferase activities.…”
Section: Discussionsupporting
confidence: 87%
“…Nsp14 may manipulate IMPDH2 to increase the phosphorylation of IKKβ and IκBα to promote nuclear translocation and phosphorylation of p65 (24). In addition, we also noticed that Nsp14 partially localizes in the nuclei of cells (Fig 1C, D), similar to findings from other groups (51,52). Thus, Nsp14 may associate with and modify the host cellular RNAs via its exonuclease and methyltransferase activities.…”
Section: Discussionsupporting
confidence: 87%
“…A prior study found the ORF10 protein colocalized with accessory proteins 7b and 8 in the endoplasmic reticulum (ER); however, its role in the ER was not described. 47 In this case, the ORF10 protein may oligomerize and form a viroporin that associates with ER membranes as a means to assist in viral replication and/or processing of other viral proteins. Alternatively, the ORF10 protein could be interacting with another protein.…”
Section: Discussionmentioning
confidence: 99%
“…Information about what each study was investigating and how we determined the ORF referred to is provided in Supplementary Table 1 . ORF called “ORF3b” in study Recommended name Study type Studies (first author and citation) 22 codon ORF ORF3b Genome report (F. Wu et al, 2020a ) Empirical ( Konno et al, 2020b ; Lokugamage et al, 2020 ; Xia et al, 2020 ; Zhang et al, 2020 ) Review Sa Ribero et al (2020) 57 codon ORF ORF3d Genome Report Chan et al (2020) Empirical ( Banerjee et al, 2020 ; Gordon et al, 2020 ; Hachim et al, 2020 ; Hayn et al, 2020 ; Lam et al, 2020 ; Laurent et al, 2020 ; Samavarchi-Tehrani et al, 2020 n.d.; St-Germain et al, 2020 ) Laboratory resource - sequence clone collection (D.-K. Kim et al, 2020a ) Computational ( Michel et al, 2020 ; Pasquier and Robichon, 2020 ; Sadegh et al, 2020 ) Review ( Celik et al, 2020 ; Garofalo et al, 2020 ; Helmy et al, 2020 ; Taefehshokr et al, 2020 ; J. Wu et al, 2020b ; Yang et al, 2020 ; Yi et al, 2020 ; Yoshimoto, 2020 ; Zinzula, 20...…”
Section: Resultsmentioning
confidence: 99%